Regulating Electronic Structure in Bi2O3 Architectures by Ti Mediation: A Strategy for Dual Active Sites Synergistically Promoting Photocatalytic Nitrogen Hydrogenation. Issue 11 (2nd May 2022) - Wu, Panfeng; Wang, Tianyu; Xue, Qi; Wang, Mengkai; Zhong, Ruihua; Hu, Jun; Chen, Zhong; Wang, Danjun; Xue, Ganglin
Abstract: Under mild conditions, nitrogen undergoes the associative pathways to be reduced with solar energy as the driving force for fixation, avoiding the high energy consumption when undergoing dissociation. Nevertheless, this process is hindered by the high hydrogenation energy barrier. Herein, Ti was introduced as hard acid into the δ‐Bi2 O3 (Ti−Bi2 O3 ) lattice to tune its local electronic structure and optimize its photo‐electrochemistry performance (reduced bandgap, increased conduction band maximum, and extended carrier lifetime). Heterokaryotic Ti−Bi dual‐active sites in Ti−Bi2 O3 created a novel adsorption geometry of O−N2 interaction proved by density functional theory calculation and N2 temperature‐programmed desorption. The synergistic effect of dual‐active sites reduced the energy barrier of hydrogenation from 2.65 (Bi2 O3 ) to 2.13 eV (Ti−Bi2 O3 ), thanks to the highly overlapping orbitals with N2 . Results showed that 10 % Ti‐doped Bi2 O3 exhibited an excellent ammonia production rate of 508.6 μmol gcat −1  h −1 in water and without sacrificial agent, which is 4.4 times higher than that of Bi2 O3 . In this work, bridging oxygen activation and synergistic hydrogenation for nitrogen with Ti−Bi dual active sites may unveil a corner of the hidden nitrogen reduction reaction mechanism and serves as a distinctive strategy for the design of nitrogen fixation photocatalysts. Abstract : Dual active sites : Ti is introduced into the δ‐Bi2 O3 lattice (Ti−Bi2 O3 ) to tune its local electronic structure. The interaction of nitrogen and the bridging oxygen in Ti−Bi local lattice realizes the activation of nitrogen, and the Ti−Bi dual active sites reduce the hydrogenated energy barrier (*NN→*NNH) from 2.65 to 2.13 eV; thus, the ammonia production rate reaches 508.6 μmol gcat −1  h −1 without sacrificial agent.